The Dystopian Reflection: A Critical Examination of Scientific Optimism in McCarthy's The Road - Adhikary, Ramesh Prasad (Academia Research Journal, 2024)
This research delves into the exploration of the detrimental impacts of science and technology on human existence through a critical analysis of Cormac McCarthy's novel, The Road. The narrative of the novel primarily revolves around the theme of propaganda and serves as a poignant portrayal of the political machinations of a totalitarian regime. The primary objective of this research is to dissect and critique the manifestation of scientific optimism in McCarthy's The Road, particularly in the context of its portrayal of the adverse effects of advanced science and technology wielded by a totalitarian government. By examining the experiences of the unnamed Man and Boy as they undertake a perilous journey in the aftermath of an unspecified global catastrophe, the study aims to unravel the profound impacts on individuals, including hunger, fear, paranoia, and a pervasive sense of identity crisis. This study examines how the use of cutting-edge science and technology by an oppressive regime has led to feelings of loss, misinterpretation, maladjustment, identity crisis, and conflict, using David Andrews' dystopian concept as a framework. The analysis involves a close examination of the novel's narrative elements, character development, and thematic content, with a specific focus on the depiction of the totalitarian government's utilization of science and technology. The findings of this research reveal a compelling critique of scientific optimism within the context of McCarthy's The Road. In conclusion, this research sheds light on the negative ramifications of scientific optimism as portrayed in McCarthy's The Road. Ultimately, The Road serves as a thought-provoking exploration of the fragile balance between progress and peril in a world shaped by the misuse of science and technology.